America yesterday & today - Hamer, Blythe (London : Carlton, 2002)
Nobody could have predicted the devastating September 11th attacks that shook the country and raised a specter of remarkable uncertainty about our history, our economy, our iconic images, and our future. At one of our country's lowest points in history, the celebration of all things American is at an all time high as we reflect on where we've been and where we're going in a context that has been irreversibly changed.
Includes index.
81032
Keywords: United States -- History -- 20th century; United States -- History -- 20th century -- Pictorial works